2022
DOI: 10.1177/17562872221128791
|View full text |Cite
|
Sign up to set email alerts
|

A review of artificial intelligence in prostate cancer detection on imaging

Abstract: A multitude of studies have explored the role of artificial intelligence (AI) in providing diagnostic support to radiologists, pathologists, and urologists in prostate cancer detection, risk-stratification, and management. This review provides a comprehensive overview of relevant literature regarding the use of AI models in (1) detecting prostate cancer on radiology images (magnetic resonance and ultrasound imaging), (2) detecting prostate cancer on histopathology images of prostate biopsy tissue, and (3) assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 208 publications
1
8
0
Order By: Relevance
“…Especially when considering the much more homogenous group of confirmed tumours in the second work. Finally, an excellent review of the application of AI techniques in classification of prostate lesions among different MRI modalities is given in [61]. The authors reported a mean sensitivity of 0.80, which is close to our results.…”
Section: Discussionsupporting
confidence: 87%
“…Especially when considering the much more homogenous group of confirmed tumours in the second work. Finally, an excellent review of the application of AI techniques in classification of prostate lesions among different MRI modalities is given in [61]. The authors reported a mean sensitivity of 0.80, which is close to our results.…”
Section: Discussionsupporting
confidence: 87%
“…Insufficient data in the development of algorithms leads to errors in performance. 16,[19][20][21][22][23][24][25][26][27][28][29][30] Underrepresentation of disease entities or population groups is likely to result in some entities not being identified correctly by the algorithm, meaning it is likely to underperform in such groups. This creates bias and an increased risk of errors in these subgroups.…”
Section: Missing Data Leading To Bias and Hidden Stratificationmentioning
confidence: 99%
“…Machine learning methods to detect aggressive/clinically significant prostate cancer on MRI can help standardize radiologist interpretations, which currently suffer from up to 34% missed aggressive prostate cancers, falsepositive rates >35%, and high inter-reader variability (κ = 0.46-0.78). [1][2][3][4] Most existing MRI-based prostate cancer detection systems [5][6][7][8][9][10][11][12][13][14] consider MRI features in a vacuum, and ignore histopathology image information. Histopathology images acquired via surgery or biopsy contain definitive information about cancer presence and aggressiveness.…”
Section: Introductionmentioning
confidence: 99%